1999
DOI: 10.1002/(sici)1520-6548(199912)14:8<791::aid-gea6>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Initial results of the southeastern Wadi Araba, Jordan Geoarchaeological Study: Implications for shifts in late quaternary aridity

Abstract: Wadi Araba is a linear valley that follows the northeast‐trending Dead Sea‐Jordan transform (DST) fault zone ca. 165 km north from the Gulf of Aqaba to the escarpment overlooking the Southern Ghor of the Dead Sea. An archaeological survey and geologic investigation was conducted along the southeast 75 km of Wadi Araba during three field seasons. The geoarchaeological study focused on analyzing sediments and soil development at sites and air photo interpretation of fluvial systems draining into Wadi Araba. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Niemi and Smith 1999). Moreover, chronologically diagnostic artifacts were not recovered from the terrace treads, perhaps indicating a very young age for their formation (cf.…”
Section: The Wadi Nukheilamentioning
confidence: 99%
See 1 more Smart Citation
“…Niemi and Smith 1999). Moreover, chronologically diagnostic artifacts were not recovered from the terrace treads, perhaps indicating a very young age for their formation (cf.…”
Section: The Wadi Nukheilamentioning
confidence: 99%
“…Despite anecdotal reports of the presence of prehistoric sites (Raikes 1980;1985), systematic surveys of the northern Araba (Mac- Donald 1992) and its southern reaches (Rothenberg 1979;Smith, Stevens, and Niemi 1997;Eichmann and Khalil 1998;Niemi and Smith 1999) appeared to support the notion that few prehistoric sites, especially those of Pleistocene age, were to be found in the Rift south of the Dead Sea. The hyperarid setting of the Araba is presumed to have curbed settlement of the region throughout prehistory.…”
Section: Introductionmentioning
confidence: 96%
“…Based on analyses of aerial photos, Garfunkel [] suggested that the Aqaba fault continues onshore from the northeast corner of the GEA through the town of Aqaba and to the east into the Edom Mountains along the valley of Wadi Yutim (Figure ). Niemi and Smith [] and Slater and Niemi [] constrained the location of the Aqaba fault between NW trending transverse faults (originally mapped by Garfunkel []) and the alluvial fan of Wadi Yutim to the east (Figure ). Mapping the locations of faults on the shelf and quantifying their deformation should help resolve how slip is transferred across the northern GEA basin.…”
Section: Previous Workmentioning
confidence: 99%
“…A normal fault (Figure ) oriented east‐west was mapped in this study between the West Aqaba Fault and the East Ayla Fault (Figure ). This fault probably belongs to an east‐west to NW trending system of transverse faults mapped by Garfunkel [] and Niemi and Smith [] (Figure ). This system of normal faults is connected to the Aqaba Fault that diverts eastward on land, similarly to the horsetail splay model [e.g., Twiss and Moores , ].…”
Section: Fault Slip Ratesmentioning
confidence: 99%
See 1 more Smart Citation